The curious incidence of monetary policy across the income distribution - Tobias Broer; John Vincent Kramer; Kurt Mitman (Sveriges Riksbank, 2022)
We use high-frequency administrative data from Germany to study the effects of monetary policy on income and employment across the earnings distribution. Earnings growth at the bottom of the distribution is substantially more elastic to policy shocks. This unequal incidence is driven by differences in the response of employment risk across the distribution: job loss is more countercyclical for lower-earnings households. Viewed through the lens of a standard incomplete-markets model, the heterogeneous incidence substantially amplifies the equilibrium response of aggregate consumption to shocks.
Keywords: 330; Geldpolitik; Wirkungsanalyse; Lohn; Haushaltseinkommen; Erwerbstätigkeit; Einkommensverteilung; Theorie